The French nation from napoleon to pétain 1814 - 1940 - Brogan, D. W. (Harper, 1957)
The French Nation describes French society as well as Frech politics during the period from the fall of Napoleon to the setting up of the Vichy government. In a century and a quarter France knew vicissitudes of victory and defeat, of glory and shame, endured invasion and revolution, and underwent a great economic and social transformation.